Early settlement and subsistence on Tongatapu, Kingdom of Tonga: Insights from a 2700–2650 cal BP midden deposit. (September 2015) - Clark, Geoffrey; Grono, Elle; Ussher, Ella; Reepmeyer, Christian
Abstract: The first significant Neolithic migration of people into the Pacific was the dispersal of Lapita culture at 3200–2850 cal BP that involved the colonization of previously uninhabited and large island groups. Population expansion was accompanied by the introduction of domesticated plants and animals, but the location and content of Lapita deposits frequently suggests that early subsistence focused on the collection of wild resources. The tension between models that advocate Neolithic migration as sustained by agricultural yields and archaeological data that disclose rapid dispersal and a reliance on indigenous resources is particularly acute in the Kingdom of Tonga. Lapita settlements located on the palaeoshoreline of Tongatapu are associated with extensive shell midden deposits suggesting the establishment of permanent settlements that were located in proximity to marine resources before human predation or a declining sea-level fall led to resource collapse and site abandonment. Analysis of a shell midden sample associated with ancient burials from Talasiu on Tongatapu suggests a small sedentary occupation that lasted a few generations 2700–2650 cal BP. Site abandonment does not appear to have been caused by a decline in marine yields and identified starch from eight food plants is the first direct evidence for a broad-spectrum mixed economy. While human predation of marine resources was substantial, sea-level fall is likely to have led to the closure of the Fanga 'Uta Lagoon at 2500 cal BP resulting in the loss of benthic habitats and the reduction of economically important marine taxa that sustained and structured early sedentism. Highlights: The first flotation study to resolve midden composition and site type in Tonga. Marine shellfish was resource that sustained and structured early settlement. The first identification of an early broad-spectrum mixed economy in Tonga. Sea level 2500 cal BP stimulated the expansion of farming in Fiji-West Polynesia.